An Anion Exchange Monolithic Cartridge for Extraction and Analysis of Oleanolic Acid from Oldenlandia diffusa - Zhu, T.; Row, K.H. (Asian Journal of Chemistry, 2013)
An anion exchange monolithic cartridge was synthesized and used for extraction and analysis of oleanolic acid from Oldenlandia diffusa. The analysis was performed on HPLC with an eluting solution consisting of methanol-water-acetic acid (88:12:0.5, v/v/v, pH = 5.8) and a C18 column. An ultrasonic-assisted process was applied to accelerate the extraction process, which was obviously increasing the extraction efficiency. Under the optimum condition, good linearity was obtained in a range of 50-2000 μg mL-1. The intra-day and inter-day were less than 4.8 and 5.7 % and recoveries were ranging from 98.3-104.5 %. This method can be used for the extraction and analysis of drugs from natural plants due to its simplicity and reliability.